Surfactant modified zeolite Y as a sorbent for some chromium and arsenic species in water - 614732 Nik Ahmad Nizam Nik Malek; Alias Mohd. Yusof; Fakulti Sains (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2007